The brine shrimp Artemia Proceedings of the International Symposium on the brine shrimp Artemia salina, Corpus Christin, Texas, USA, August 20-23, 1979 - Persoone, G.; Sorgeloos, P.; Roels, O.; Jaspers, E. (Belgium Universas Press Wetteren, 1980)
content: vol. 3 Ecology, culturing and use in aquaculture
Keywords: Artemia salina; Brine shrimp